Froggy goes to the doctor - London, Jonathan, 1947-; Remkiewicz, Frank (New York : Viking, 2002)
Froggy isn't looking forward to his check-up because he might get a shot but when it's over and he's pronounced a very healthy frog, Dr. Mugwort is the one who dreads Froggy's next visit.
Horn Book.
Kirkus Review.
Wilson's Children.
4.3.
4.3
K-3
Keywords: Frogs -- Fiction; Humorous stories; Medical care -- Fiction; Physicians -- Fiction; Frogs -- Fiction; Humorous fiction; Medical care -- Fiction; Physicians -- Fiction